Physiological Role of Chlorinated Aryl Alcohols Biosynthesized De Novo by the White Rot Fungus Bjerkandera sp. Strain BOS55 - de Jong, Ed (1994)
The white rot fungus Bjerkandera sp. strain BOS55 produces veratryl, anisyl, 3-chloroanisyl, and 3,5-dichloroanisyl alcohol and the corresponding aldehydes de novo from glucose. All metabolites are produced simultaneously with the extracellular ligninolytic enzymes and have an important physiological function in the fungal ligninolytic system. Both mono- and dichlorinated anisyl alcohols are distinctly better substrates for the extracellular aryl alcohol oxidases than veratryl alcohol. The aldehydes formed are readily recycled by reduction by washed fungal mycelium, thus creating an extracellular H(2)O(2) production system regulated by intracellular enzymes. Lignin peroxidase does not oxidize the chlorinated anisyl alcohols either in the absence or in the presence of veratryl alcohol. It was therefore concluded that the chlorinated anisyl alcohols are well protected against the fungus's own aggressive ligninolytic enzymes. The relative amounts of veratryl alcohol and the chlorinated anisyl alcohols differ significantly according to the growth conditions, indicating that production of veratryl alcohol and the production of the (chlorinated) anisyl metabolites are independently regulated. We conclude that the chlorinated anisyl metabolites biosynthesized by the white rot fungus Bjerkandera sp. strain BOS55 can be purposefully produced for ecologically significant processes such as lignin degradation.